Cattle naturally infected by Eurytrema coelomaticum: Relation between adenosine deaminase activity and zinc levels. (February 2017) - Grosskopf, Hyolanda M.; Schwertz, Claiton I.; Machado, Gustavo; Bottari, Nathieli B.; da Silva, Ester S.; Gabriel, Mateus E.; Lucca, Neuber J.; Alves, Mariana S.; Schetinger, Maria Rosa C.; Morsch, Vera M.; Mendes, Ricardo E.; da Silva, Aleksandro S.
Abstract: The enzyme adenosine deaminase (ADA) is critical for modulating the immune system, and in the presence of zinc, its activity is catalyzed. The aim of this study was to evaluate the ADA activity in pancreas of cattle naturally infected by Eurytrema coelomaticum in relation to the results of zinc levels, pathological findings and parasite load. For this study 51 slaughtered cattle were used. The animals were divided into two groups: Group A consisting of animals naturally infected by E. coelomaticum (n = 33) and Group B of uninfected animals (n = 18). Blood and pancreas were collected of each animal for analysis of zinc and ADA, respectively. Infected cattle showed a reduction on seric levels of zinc, and decreased ADA activity in the pancreas (P > 0.05). A positive correlation between zinc levels and ADA activity was observed. Thus, high parasite load and severity of histopathologic lesions affect the ADA activity in pancreas, as well as the zinc levels in serum of infected animals (negative correlation between these variables). Therefore, we can conclude that cattle infected by E. coelomaticum have low ADA activity in pancreas, which can be directly related to zinc reduction, responsible for ADA activation and catalyzes. Highlights: Eurytrema usually parasitize the pancreatic ducts. The enzyme ADA is critical for modulating the immune system. In the presence of zinc, ADA activity is catalyzed. Cattle infected by E. coelomaticum have low ADA activity in pancreas. Zinc levels reduction may be related with ADA activity in pancreas.